Analisis Stabilitas Dinding Penahan Tanah Tipe Mechanically Stabilized Earth (MSE) Wall Terhadap Curah Hujan - Hidayat, Wirman (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2021)
The rainfall is a factor that has a significant effect on the stability of the retaining wall. In this paper, a study was conducted on the effect of rainfall intensity and duration on the stability of the Mechanically Stabilized Earth (MSE) wall indicated by the number of the safety factors. The variations were made on the rate of the rainfall intensity, namely the intensity of normal, heavy, and extremely heavy rain, then variations were also made on the duration of the rain, namely 12, 24, 36, 48, 72, and 96 hours. The analysis was carried out using the software PLAXIS 2D finite element method with the type of calculation of fully coupled flow-deformation analysis. The analysis begins with an analysis of the safety factor was carried out on the construction process and the operational loading conditions of the MSE wall, the results obtained that the wall was in a stable condition with a safety factor for the long term 1.87. The next step is to analyze the effect of rain intensity and duration on the stability of the MSE wall, it was found that there is a decrease in safety factor due to rainfall intensity for a certain duration. Normal rain intensity results in a safety factor that is always above the safety criteria for the specified rain duration, while in heavy and extremely heavy rain the safety factors are below the minimum safety criteria after the rain duration of more than 24 hours and 12 hours, respectively. The decrease in safety factor is caused by several factors, such as an increase in pore water pressure, an increase of soil saturation, and a decrease in the suction pressure which affects the effective stress as a parameter that determines soil strength.